Tipologi Rumah Kampung Gandekan Kota Semarang - Gregorius Gravido Praha Prayogo; Edward Endrianto Pandelaki; Bangun Indrakusumo Radityo Harsritanto (RUAS, 2022)
Gandekan has an interesting problem to be used as an object of research due to its own uniqueness as one of the urban villages which is related to the history of the city of Semarang, while on the other hand, it is currently facing various problems both socially, economically and culturally. As time progresses, the historic Gandekan old houses began to be marginalized due to the foreign culture that entered the city of Semarang. The typology or characteristics of these houses are beginning to disappear based on field studies of old houses in the village of Semarang. So that, the field studies and grouping characteristics of the buildings were carried out to answer the research, in hope that the characteristics of the old house of the Gandekan village community can be preserved in the midst of cultural development.